2010
DOI: 10.1088/0067-0049/186/2/485
|View full text |Cite
|
Sign up to set email alerts
|

ERRATUM: “LOW-RESOLUTION SPECTROSCOPY OF GAMMA-RAY BURST OPTICAL AFTERGLOWS: BIASES IN THE SWIFT SAMPLE AND CHARACTERIZATION OF THE ABSORBERS” (2009, ApJS, 185, 526)

Abstract: Low-resolution spectroscopy of gamma-ray burst optical afterglows: Biases in the swift sample and characterization of the absorbers http:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
288
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(312 citation statements)
references
References 0 publications
22
288
2
Order By: Relevance
“…Our calculated escape fraction, f esc = 1.0 per cent, is somewhat smaller than recent estimates have suggested. In particular, it falls short of the 2 ± 0.3 per cent derived by Chen et al (2007) from reasonable extrapolation of the observed GRB–DLA statistics (see also Fynbo et al 2009); this is a reflection of our previously described underestimate of the abundance of absorbers in the observational bin 10 17 < N H i /cm −2 < 10 19 . More worryingly, our derived fraction is very sensitive to assumptions we make about launching the GRB sightlines; for instance, adding a 200 pc Gaussian random offset to our stellar particle loci raises the fraction to f esc = 2 per cent.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Our calculated escape fraction, f esc = 1.0 per cent, is somewhat smaller than recent estimates have suggested. In particular, it falls short of the 2 ± 0.3 per cent derived by Chen et al (2007) from reasonable extrapolation of the observed GRB–DLA statistics (see also Fynbo et al 2009); this is a reflection of our previously described underestimate of the abundance of absorbers in the observational bin 10 17 < N H i /cm −2 < 10 19 . More worryingly, our derived fraction is very sensitive to assumptions we make about launching the GRB sightlines; for instance, adding a 200 pc Gaussian random offset to our stellar particle loci raises the fraction to f esc = 2 per cent.…”
Section: Resultsmentioning
confidence: 65%
“…For such systems, it is possible to determine observationally the column density of neutral hydrogen. We compiled a list of N H i ‐values for 38 GRB–DLAs in the redshift interval 2 < z < 4 by combining data from Jakobsson et al (2006), Chen et al (2007) and Fynbo et al (2009). We caution that, unlike for the QSO–DLAs for which homogeneous catalogues are available (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fynbo et al 2001; Lazzati, Covino & Ghisellini 2002; Jakobsson et al 2004; Levan et al 2006a; Rol et al 2007; Perley et al 2009) dust destruction by X‐rays could still be effective enough to allow UV/optical observations of the afterglow according to Fruchter, Krolik & Rhoads (2001). However, Fynbo et al (2009) suggests very convincingly that dark bursts may not be representative of the general GRB population, and trace different environmental properties than bursts with detected optical afterglows. Either way, even in the absence of any transient optical emission it is possible to identify a redshift for a GRB from its X‐ray identified host galaxy (e.g.…”
Section: Selection Effectsmentioning
confidence: 99%
“…GRB 071025, detected by the Swift mission (Gehrels et al 2004), provides among the best probes of the early‐time behaviour of a GRB to date. While no secure spectroscopic redshift was attained [ z ∼ 5.2 was estimated from a low‐quality High Resolution Echelle Spectrometer (HIRES) optical spectrum at Keck; Fynbo et al 2009], the photometric SED presented here shows clear evidence of a Lyman α break in the observer‐frame R band and indicates a photometric redshift of 4.4 < z < 5.2 (), making this among the highest redshift bursts to date and one of only a few observed in simultaneous colours during prompt emission. Our infrared (IR) and optical observations start at ∼30 s after the burst in the rest frame and follow the rise, peak and fall of an afterglow in simultaneous rest‐frame optical colours.…”
Section: Introductionmentioning
confidence: 99%